2017
DOI: 10.18203/2320-6012.ijrms20171854
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and its association with anthropometric parameters in adult population of Raipur city, Chhattisgarh, India

Abstract: Background: Obesity is now an important emerging public health problem in India. It is one of the major risk factor for hypertension. Overweight persons have two to six fold increase in the risk of developing hypertension. This study was carried out with objective to find out prevalence of Hypertension and assess its association with four obesity-related indices- body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR).Methods: A cross-sectional community-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…These findings were similar to study carried out by Midha et al ,[ 48 ] Kokiwar et al ,[ 47 ] and Panda et al . [ 57 ] in their respective study area.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were similar to study carried out by Midha et al ,[ 48 ] Kokiwar et al ,[ 47 ] and Panda et al . [ 57 ] in their respective study area.…”
Section: Discussionmentioning
confidence: 99%
“…HTN was found to be associated with abdominal obesity as defined by waist-hip ratio and WC ( p = 0.000 and p = 0.000, respectively). Previous studies had shown obesity to be an important risk factor for HTN (Dua et al , 2014; Oladoyinbo et al , 2015; Panda et al , 2017). HTN in this study was significantly higher ( p = 0.019) among respondents that consume alcohol and no significant association was observed between DM and HTN ( p = 0.78).…”
Section: Resultsmentioning
confidence: 99%
“…One more study done in Department of Community Medicine, Pt. Jawahar Lal Nehru Memorial Medical College, Raipur, Chhattisgarh, India by Panda et al [18] in the year 2017 and it was concluded that there is a rising burden of hypertension among study population and waist hip ratio was strongly associated with hypertension. From the various studies conducted in the direction [19][20][21][22][23] results seem to be compatible with the outcome of our study, though smaller sample size and lake of gender wise data, have been the major limitations of our study.…”
Section: Discussionmentioning
confidence: 99%